A Study on Changes Made in Housekeeping and Front Office in Hotel Radisson Blu Tower, Kaushambi Post Covid-19 (Global Journal of Management and Business Research, 2022)
There have been many changes and challenges Post COVID-19 in which hospitality industry have suffered a lot and is trying to cope up with the scenario. The hoteliers are playing a very crucial role by taking care of themselves and the guest#x2019;s health. Hotels have gone through lot of challenging faces to make their guest feel the warmth of hospitality by even maintaining up the social distancing. The hotel is following the new SOP#x2019;s Post Covid 19 like luggage sanitization, hand sanitizers kept at entrance, 6-feet social distancing is maintained, plexi glass wall is fixed at front desk, separate pen holders for used and unused pen, stickers are stuck to floor to maintain the minimum distancing standards. Moreover, apart from front area SOPs are also being followed at back of the house like social distancing hand sanitizers, session being held regularly to motivate staff for maintaining the distancing and following the SOPs Post COVID-19After the Covid-19 pandemic, all the procedures have been taken in view of the health of all the guests as well as the health of the staff. The guests are happy to see that their health is being taken care of.
Keywords: customer preference; covid-19; hospitality industry; front office